Hospital Lighting in Tropical and Temperate Contexts: Nursing Staff Perceptions and Design Implications - Ludmila C. F. Mendes; Roberta V. G. Souza; Raphael D. Pais; Sofia B. Moreira; Natalia Sokol (Buildings, 2026)
This study compared nursing professionals’ perceptions of the luminous environment in hospital nursing stations located in tropical (Brazil) and temperate (Poland) contexts. Data was collected through online questionnaires addressing work shifts, architectural and lighting characteristics, users’ perceptions and preferences regarding daylighting and electric lighting. The questionnaire was created in Google Forms and included multiple-choice and matrix questions. Satisfaction and perceived relevance were measured using a Likert scale. The survey received responses from 391 nursing professionals in Brazil and 139 in Poland. Significant differences were found in the architectural and lighting characteristics of nursing stations. The questionnaires were analysed using descriptive statistics, Cronbach’s alpha coefficient, non-parametric tests for group comparisons. Despite Brazil’s high daylight availability, nursing stations without windows were considerably more common in Brazil (41%) than in Poland (10%). Preferences for electric lighting also differed, with Brazilian respondents favouring neutral correlated colour temperatures (CCTs) and Polish respondents preferring warmer CCTs. A mismatch between satisfaction and perceived importance was identified for several lighting attributes, particularly glare control and electric lighting colour temperature. Access to outdoor views and lighting control were highly valued. The findings suggest that architectural design decisions may exert greater influence on nurses’ light exposure than local climatic conditions.